PMP--practice makes perfect : over 1000 PMP practice questions and answers - Estrella, John. (Hoboken, N.J. : Wiley, 2012)
A study guide for the Project Management Professional (PMP) exam.
Includes index.
Keywords: Project management -- Examinations, questions, etc